Partial collapses experienced for a steel space truss roof structure induced by ice ponds - Piroglu, Filiz; Ozakgul, Kadir; Özakgül, Kadir (Elsevier BV, 2016)
Abstract This paper presents investigations on the steel space truss roof of an industrial plant collapsed partially after exceptional snowfalls. This low sloped light weight roof structure supported on steel columns of 16.3 m height and covering totally 26,080 m2 closed area in plan was constructed as Mero type double layer grid steel space truss system having a height of 2 m. Also, parapets of 90 cm height were placed along the perimeter of the building and siphonic system was used for roof drainage. To find out the main reasons of the partial collapse of the roof structure, a site investigation was conducted and findings were collected, then conformity of the structural members were checked with respect to the current Turkish steel building design codes. The material properties of the primary load carrying members of the roof were scrutinized by performing tensile tests. Finally, it was understood that two unexpected catastrophic collapses were experienced as a consequence of ice ponds that occurred on the edge regions of the roof due to discontinuously heated roof parts by the radiant heaters mounted on the roof structure and the freezing of the siphonic system.